(untitled) (Geologica Macedonica, 2022)
The present study was performed to describe an occurrence of very big crystals of brucite and its associated minerals in locality of ’Ržanovo. It was also intended to describe the conditions of crystallization of such a big crystal. Within highly altered peridotite host rock in ‘Ržanovo region, acicular, up to 80 cm in size, colorless crystals of brucite were found. It has been also found as small, and in some places large lenses filled with acicular brucite. Crystals were found in serpentinized ultrabasic rocks, within veins. Needles are perpendicular to vein walls. Chemical composition is determinated with ICP-MS. MgO (66.39–69.13), Al2O3 (0.343–0.601), FeO (1.956–4.025), MnO2 (0.239–0.360), TiO2 (0.003–0.009), LOI (25.1–27.4). Its unit cell is: a = 3.1458 (7), c = 4.766 (2) Å (rhombo-hedral a = 2,4130 Å, α = 81.36°), V = 40.84 (2) Å3, Z = 1.